1992
DOI: 10.1093/nar/20.16.4319
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen induced mutation spectrum in mammalian cells

Abstract: In order to characterize the molecular nature of singlet oxygen (1O2) induced mutations in mammalian cells, a SV40-based shuttle vector (pi SVPC13) was treated with singlet oxygen arising from the thermal decomposition of the water-soluble endoperoxide of 3,3'-(1,4-naphthylidene) dipropionate (NDPO2). After the passage of damaged plasmid through monkey COS7 cells, the vector was shuffled into E. coli cells, allowing the screening of supF mutants. The mutation spectrum analysis shows that single and multiple ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Moreover, the nucleotide transition of G:C to A:T or A:T to G:C and transversion of A:T to C:G were more prevalent in the AKR1B8 deficient mucosa. These changes are consistent with oxidative and carbonyl-induced DNA damage (10, 39). Therefore, the increased inflammatory cytokines and cellular and DNA damage induced by oxidative stress and lipid peroxides provide a mechanism for many of the events that drive the severity of UC and the progression of UC to cancer in this mouse model.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, the nucleotide transition of G:C to A:T or A:T to G:C and transversion of A:T to C:G were more prevalent in the AKR1B8 deficient mucosa. These changes are consistent with oxidative and carbonyl-induced DNA damage (10, 39). Therefore, the increased inflammatory cytokines and cellular and DNA damage induced by oxidative stress and lipid peroxides provide a mechanism for many of the events that drive the severity of UC and the progression of UC to cancer in this mouse model.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, nucleotide transition of G:C to A:T ( P < 0.05) or A:T to G:C ( P < 0.01) and transversion of A:T to C:G ( P < 0.05) were more prevalent in AKR1B8 −/− colitis and tumors compared to WT colits (Fig. 6C), consistent with the oxidative and carbonyl-induced DNA damage (10, 39). …”
Section: Resultssupporting
confidence: 66%
“…In addition, the mutagenesis spectrum of point mutations is compatible with oxidative stress-induced mutagenesis. Indeed, the strong increase in GC to CG transversions is a signature of oxidative damage by singlet oxygen 17 18 19 . In particular, the oxidation of 8-oxoguanine can form imidazolone, guanidinohydantoin or spiroiiminodihydantoin, which could be responsible for GC to CG transversions 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Again, RB's potential for mutagenicity was not assessed [17]. Because RB can enter living cells and stain the nucleus, this raises questions about mutagenicity, especially since studies have demonstrated that byproducts of Rose Bengal are capable of interacting with and damaging DNA [18,19]. This study examines the cytotoxicity and mutagenicity associated with photoactivated RB in hopes of gaining a better insight into the potential hazards associated with the use of RB in PTB procedures.…”
Section: Introductionmentioning
confidence: 99%